COMMON LABORATORY DIAGNOSTIC DATA ANALYSIS OF PATIENTS WITH DUPUYTREN’S CONTRACTURE AT THE STAGES OF PATHOLOGICAL PROCESSES IN PALM APONEUROSIS - Guryev, S.O.; Iskra, N.I.; Kuzmin, V.Y.; Tanasienko, P.V. (World of Medicine and Biology, 2020)
The study of the characteristic features of laboratory data in patients with Dupuytren’s contracture, which in the past was verified as having been exposed to ionizing radiation, showed that in the examined patients with Dupuytren’s contracture there is a concordance of the fibrous process in the palmar aponeurosis and liver, and the pathological process in the liver is one of the primary pathogenetic links in the formation of contracture. It was revealed that there is a relationship between the degree of fibrous liver damage and the biochemical blood parameters of patients with Dupuytren’s contracture.